2001
DOI: 10.1007/s00256-001-0450-3
|View full text |Cite
|
Sign up to set email alerts
|

Chondroblastoma and clear cell chondrosarcoma: radiological and MRI characteristics with histopathological correlation

Abstract: Objective: To analyze and compare the radiological and magnetic resonance imaging (MRI) appearances of chondroblastoma and clear cell chondrosarcoma with histopathological correlation. Design and patients: Twelve patients with histologically proven chondroblastoma and of another four patients with clear cell chondrosarcoma were investigated by radiographs and MRI (T1-, T2-weighted sequences, intravenous gadolinium application). Additionally, the clinical and radiologic data of seven cases of clear cell chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(50 citation statements)
references
References 19 publications
(29 reference statements)
2
46
0
2
Order By: Relevance
“…Bone-marrow edema extending to the circumference of the tumor is observed in 82-92% of cases on MRI, and soft-tissue edema is also found in 58-82% of cases [15,16,23]. Approximately 30% of cases are associated with joint effusion as demonstrated by MRI [15,16,25]. In our study, the frequency of inflammatory reaction was similar to previously reported data.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Bone-marrow edema extending to the circumference of the tumor is observed in 82-92% of cases on MRI, and soft-tissue edema is also found in 58-82% of cases [15,16,23]. Approximately 30% of cases are associated with joint effusion as demonstrated by MRI [15,16,25]. In our study, the frequency of inflammatory reaction was similar to previously reported data.…”
Section: Discussionsupporting
confidence: 92%
“…A thick-solid or layered-type periosteal reaction distant from the lesion itself has been found in 20-90% of cases of chondroblastoma on radiography or MRI [2,3,4,8,12,13,15,16,23,25]. Bone-marrow edema extending to the circumference of the tumor is observed in 82-92% of cases on MRI, and soft-tissue edema is also found in 58-82% of cases [15,16,23]. Approximately 30% of cases are associated with joint effusion as demonstrated by MRI [15,16,25].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Radiographically, giant cell tumors differ from chondroblastomas as purely radiolucent lesions without the intralesional calcification present in chondroblastomas. Additionally, the flare phenomenon found in chondroblastomas is less prominent in giant cell tumors [13,17,24]. Histologically, the main differentiating characteristic is cartilage matrix.…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…Histologically, approximately one-third of cases have foci of secondary aneurysmal bone cyst (ABC) [6], which may present as areas of fluid signal-intensity or fluid-fluid levels within the tumor on MRI [12,13]. Pain is the presenting symptom in most patients, with swelling, limp, joint stiffness, and a soft tissue mass also reported [14].…”
Section: Introductionmentioning
confidence: 97%